PENGEMBANGAN MEDIA PEMBELAJARAN IPAS DALAM BENTUK VIDEO PEMBELAJARAN BERBASIS CANVA PADA MATERI PENGELOLAAN SAMPAH KELAS V SD NEGERI CIMONE 1 KOTA TANGERANG - Nurliyyah, Siti Rohmah; Magdalena, Ina; Hartantri, Saktian Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop an Integrated Science and Social Studies (IPAS) learning media in the form of a Canva-based instructional video on waste management material for fifth-grade students at SD Negeri Cimone 1 and to determine the validity, practicality, and effectiveness of the developed media. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included media experts, language experts, material experts, education experts (teachers), and fifth-grade students of SD Negeri Cimone 1. Data were collected through observation, interviews, questionnaires, documentation, and learning achievement tests the data were analyzed using descriptive quantitative analysis with a Likert scale and percentage-based feasibility assessment. The results showed that the developed learning media met the criteria of being valid, practical, and effective. The validation results indicated an average score of 4 from the media expert, 4,3 from the language expert, 4.73 from the material expert, and 4,73 from the education expert, resulting in an overall validity level of 94%, which falls into the very valid category. The implementation results demonstrated highly positive responses from students. The one-to-one trial obtained an average score of 4,3, the small-group trial achieved 4.50, and the medium-group trial reached 4,71, with an overall practicality level of 94.3%, categorized as very practical. Furthermore, the learning achievement test indicated an improvement in students' learning outcomes after using the instructional video, confirming that the developed media was effective for teaching waste management material in the IPAS subject. Based on these findings, it can be concluded that the Canva-based instructional video for IPAS learning is feasible for classroom implementation as it fulfills the criteria of validity, practicality, and effectiveness, learning motivation in waste management lessons.